Drift in Producer Price Indexes for the Former Soviet Union (FSU) Countries - Zieschang, Kimberly (IMF Working Papers; Working Paper ;, 1994)
The purpose of this paper is to show that, under the price fluctuations that characterize most transition economies, the commonly used chain index derived from the published month-to-month price change of the PPI in some cases dramatically overstates the rate of price inflation. The analysis is based in part on a seminal paper by Szulc, who studies the problem of drift for a wide class of index formulae, and in part on the observations of price movements made by the Fund's missions. Greatest during the year 1992, the drift declines with slower rates of inflation and, possibly, with changing patterns of price increases, but is still important for countries such as Russia, where monthly inflation continues to run well into the double digits.